Preparação e caracterização de eletrodos de polímeros condutores sobre carbono vítreo reticulado (RVC) para a aplicação em baterias secundárias - Dalmolin, Carla (Universidade Federal de São Carlos, 2006)
The general purpose of this work is the optimization of the conducting polymer deposition on RVC and the use of these electrodes in an allpolymeric ion-lithium battery, which means an anode and a cathode made of conducting polymers. Several steps were done in order to attain this purpose: i) a previous study on the effect of different pre-treatments on the RVC surface; ii) the optimization of the deposition (chemical or electrochemical) procedures of conducting polymers on RVC; iii) the investigation of the influence of different kinds of deposition on the properties of the conducting polymers; iv) the study about the effect of different dopants on the electrochemical and morphological properties of the polymers; and v) the verification of the electrode performance as anode or cathode in an ion-lithium battery. The results lead to the conclusion that the ohmic drop effects and low current penetration, a characteristic of the tridimensional RVC electrodes, can be minimized by using thinner electrodes, which is crucial specially for conducting polymer films obtained by electropolymerization. The high surface area of these materials influenced positively on the electrochemical behavior of the electrodes, leading to high-specific capacity electrodes when compared to similar bidimensional electrodes. However, to enable the investigation of these electrodes by Electrochemical Impedance Spectroscopy, the proposition of a new equivalent electrical circuit was done considering two different electrochemical environments (at the inner and outer substrate surfaces). Chargedischarge tests for batteries using RVC/polymer electrodes as the cathodic material showed similar or even higher specific capacities than the ones found in the literature. It is believed that the substrate s high surface area is the responsible for these findings, since it facilitates the redox reactions in the polymers.
Preparation and characterization of conducting polymer electrodes on reticulated vitreous carbon (RVC) for application in secondary batteries
Keywords: Eletroquímica; Polímeros condutores; Carbono vítreo reticulado; Baterias de íons-lítio; CIENCIAS EXATAS E DA TERRA::QUIMICA